2016
DOI: 10.1002/rcm.7668
|View full text |Cite
|
Sign up to set email alerts
|

Collision‐induced dissociation of uranyl‐methoxide and uranyl‐ethoxide cations: Formation of UO 2 H + and uranyl‐alkyl product ions

Abstract: UO2 H(+) is generated from [UO2 OCH3 ](+) by transfer of H from the methyl group. Variable-energy and variable-time CID experiments suggest that the apparent threshold for production of UO2 H(+) is lower than for UO2 (+) , but the pathway is kinetically less favored for the former than for the latter. CID experiments reveal that [UO2 OCH2 CH3 ](+) dissociates to generate [UO2 CH3 ](+) , a relatively rare species with a U-C bond, and [UO2 (O = CH2 )](+) .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 54 publications
2
9
0
Order By: Relevance
“…CID of [U VI O 2 (ClO 4 )(H 2 O)] + (MS 4 stage, Figure C), created [U VI O 2 (ClO 4 )] + ( m/z 369) by loss of the final H 2 O ligand, and all of the fragmentation reactions to this point were in general agreement with the earlier study that used a 3D ion trap . One notable difference, however, was that the number and relative abundance of H 2 O was significantly lower in the present experiments, consistent with several recent studies by our group …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…CID of [U VI O 2 (ClO 4 )(H 2 O)] + (MS 4 stage, Figure C), created [U VI O 2 (ClO 4 )] + ( m/z 369) by loss of the final H 2 O ligand, and all of the fragmentation reactions to this point were in general agreement with the earlier study that used a 3D ion trap . One notable difference, however, was that the number and relative abundance of H 2 O was significantly lower in the present experiments, consistent with several recent studies by our group …”
Section: Resultssupporting
confidence: 92%
“…Elimination of HClO 4 was confirmed by noting the shift in neutral loss from 99 to 101 mass units following CID of the 37 Cl isotopic peak (data not shown). CID of the peak at m/z 301 (spectrum not shown) led primarily to product ions at m/z 270 and 271, consistent with an earlier study by our group of the CID of [U VI O 2 (OCH 3 )] + normalUVInormalO2ClO4CH3OH+normalUVInormalO2OCH3++HClO4 …”
Section: Resultssupporting
confidence: 89%
“…We found that sufficient abundance of ethanol‐coordinated uranyl‐ethoxide cation, [UO 2 (OCH 2 CH 3 )(CH 3 CH 2 OH) 2 ] + , was created by ESI of the uranyl‐acetate solution (in 50:50 H 2 O:CH 3 CH 2 OH) to allow preparation of [UO 2 (OCH 2 CH 3 )] + by MS n CID. Subsequent CID of [UO 2 (OCH 2 CH 3 )] + created [UO 2 (CH 3 )] + …”
Section: Resultsmentioning
confidence: 99%
“…Recent experiments by our group have demonstrated that lower levels of adventitious H 2 O in a linear ion trap (LIT) mass spectrometer can provide access to fragmentation pathways and reactions for gas‐phase uranyl (U VI O 2 2+ ) complexes that were not observed during previous experiments conducted with a three‐dimensional quadrupole ion trap (QIT) . When H 2 O levels in an ion trap are high, precursor complexes that are isolated for collision‐induced dissociation (CID) tend to undergo association reactions to make adducts or charge reduction reactions to form products such as [UO 2 (OH)] + , [UO 2 ] + , and hydrates of these cations .…”
Section: Introductionmentioning
confidence: 99%
“…Recent experiments by our group have shown that low levels of residual H 2 O in a linear ion trap (LIT) mass spectrometer make possible the study of fragmentation pathways and intrinsic reactions of gas‐phase uranyl (U VI O 2 2+ ) complexes that were not observed during previous experiments conducted with a three‐dimensional quadrupole ion trap (QIT) 1–7 . When H 2 O levels in an ion trap are high, precursor complexes that are isolated for collision‐induced dissociation (CID) tend to undergo association reactions to make adducts, or charge reduction reactions to form products such as [UO 2 (OH)] + , [UO 2 ] + , and hydrates of these cations 8–12 .…”
Section: Introductionmentioning
confidence: 99%